2019
DOI: 10.1016/j.ijid.2018.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of hepatitis B vaccine booster in children born to HBsAg-positive mothers in rural China

Abstract: Objective: In rural areas of China with highly endemic for hepatitis B virus (HBV) infection, protective efficacy was observed in adulthood when a one-dose HBV vaccine booster was administered to high-risk children born to mothers who were positive for hepatitis B surface antigen (HBsAg). The aim of this study was to estimate the cost-effectiveness of an HBV vaccine booster in this specific group of children when given at 10 years of age. Methods: Two potential strategies were considered: strategy 1 was a one-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…There were concerns about the vaccine escape related aa substitutions could threaten the effectiveness of HBV vaccine, but the most recent epidemiology data: HBV infection rate among children under five declined from 9.67% in 1992 to 0.32% in 2014, strongly supported the effectiveness of current immunize strategy. 13 Our previously publication about quasispecies characters in infants and their mothers also proved vaccine-escaped variants sourced from their mothers, rather than from the breakthrough after vaccination. 14 serum from infant patients were collected and analyzed, so seroepidemiology information of mother carriers was missed in this study.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…There were concerns about the vaccine escape related aa substitutions could threaten the effectiveness of HBV vaccine, but the most recent epidemiology data: HBV infection rate among children under five declined from 9.67% in 1992 to 0.32% in 2014, strongly supported the effectiveness of current immunize strategy. 13 Our previously publication about quasispecies characters in infants and their mothers also proved vaccine-escaped variants sourced from their mothers, rather than from the breakthrough after vaccination. 14 serum from infant patients were collected and analyzed, so seroepidemiology information of mother carriers was missed in this study.…”
Section: Discussionmentioning
confidence: 90%
“…There were concerns about the vaccine escape related aa substitutions could threaten the effectiveness of HBV vaccine, but the most recent epidemiology data: HBV infection rate among children under five declined from 9.67% in 1992 to 0.32% in 2014, strongly supported the effectiveness of current immunize strategy …”
Section: Discussionmentioning
confidence: 99%
“…The first study concluded that boosters delivery in adolescents might be appropriate for high-risk individuals who were born to HBsAg-positive mothers when children's serum anti-HBs <10 mIU/mL; the second study found that HBV vaccine booster given to children born to HBsAg-positive mothers in rural China would be cost-effective and could be considered in HBV endemic areas. 82,83 However, cost-effectiveness of these additional vaccination strategies is an important consideration. For individuals with chronic HBV infection, cirrhosis or other worse conditions, antiviral therapy using nucleot(s)ide analogues are recommended when a patient's serum alanine transaminase was elevated.…”
Section: Primary Preventionmentioning
confidence: 99%
“…Two local studies have also assessed the effect of a HBV booster vaccine dose delivered to adolescents at risk. The first study concluded that boosters delivery in adolescents might be appropriate for high‐risk individuals who were born to HBsAg‐positive mothers when children's serum anti‐HBs <10 mIU/mL; the second study found that HBV vaccine booster given to children born to HBsAg‐positive mothers in rural China would be cost‐effective and could be considered in HBV endemic areas 82,83 . However, cost‐effectiveness of these additional vaccination strategies is an important consideration.…”
Section: Recommendations In Comprehensive Control Of Liver Cancermentioning
confidence: 99%
“…Although HBV vaccine is available and is the most effective strategy to prevent HBV infection (Wang et al, 2018(Wang et al, , 2019Zhu et al, 2018), only 26.2% (95% CI: 21.1-31.4) of the studied population was positive for isolated anti-HBs over 10 mIU/mL (serological HBV vaccination like profile). Age under 26 years associated with the immune response to HBV vaccine was expected, since free hepatitis B vaccine has been provided to all newborns and to high-risk individuals since 1999 and gradually extended to older ages.…”
Section: Discussionmentioning
confidence: 98%